2022
DOI: 10.1002/mar.21649
|View full text |Cite
|
Sign up to set email alerts
|

Autonomy and control: How political ideology shapes the use of artificial intelligence

Abstract: Leveraging the context of artificial intelligence (AI)‐enabled checkouts (e.g., Grab‐and‐Go checkouts), we show that, across four studies, consumer response depends on their political identity salience: consumers with higher political identity salience (vs. the uninvolved) evaluate and respond to retailers using AI‐enabled checkouts more favorably compared with self‐service kiosks. Moreover, among these consumers, we propose and find political ideology as a boundary condition; liberals prefer AI‐enabled over s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 68 publications
0
17
0
Order By: Relevance
“…It would also be interesting to relate our work relates to others. For example, Cui Van Esch (2022) reported that liberal consumers opt for grab‐and‐go checkouts because such checkout processes offer them greater autonomy, which liberal consumers value. Our findings provide an alternate mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It would also be interesting to relate our work relates to others. For example, Cui Van Esch (2022) reported that liberal consumers opt for grab‐and‐go checkouts because such checkout processes offer them greater autonomy, which liberal consumers value. Our findings provide an alternate mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…For example, uncertainty avoidance is likely a defining characteristic of conservatives (Chan & Ilicic, 2019; J. Jung & Mittal, 2020), partly stemming from the conservative consumer's preference for status quo (Eidelman et al, 2012). Similarly, because approach emotions (i.e., emotions motivating approach behavior such as desire, delight, and excitement) are consistent with liberalism, consumers who identify as left‐leaning or liberal express a preference for AI‐enabled rather than self‐checkouts (Cui & van Esch, 2022). Moreover, conservatives respond differently to LGBT imageries in advertising relative to liberals since such imagery evokes different emotions (Northey et al, 2020).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…However, little research has been extended on this investigation to understand the effect beyond personality. Political ideology is one such concept that could assist in providing such insight (Cui and van Esch, 2022; Northey et al. , 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has identified that a consumer's political ideology underpins their emotional reactions (Northey et al, 2020), their attitudes (Kaikati et al, 2017) and their behaviours (Crockett and Wallendorf, 2004). Although it has been identified that political ideology is a key determinant of how one will respond to stimuli, research is only just emerging which examines how political ideology may assist in explaining one's reaction to technology and in particular AI (Cui and van Esch, 2022;Mak et al, 2021). Mack et al (2021) provide initial support of this relationship where they identified political ideology-influenced autonomous vehicle adoption.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research shows that American religions are increasingly dividing into the two major political parties, with evangelical Christians providing the activist base of the Republican Party, while secularists and liberals lean toward the Democratic Party (Carlisle & Clark, 2017 ; Green et al, 1996 ; Kellstedt et al, 1991 ). In particular, one’s political ideology moderates various socially related behavior such as the intention to donate during the COVID-19 pandemic (van Esch et al, 2021 ); LGBT imagery in advertising (Northey et al, 2020 ; Shepherd et al, 2021 ); responses to surge price precision (Cui et al, 2022 ) and the use of artificial intelligence (Cui & van Esch, 2022 ). Specific to climate change belief, McCright ( 2011 ) summarized that political orientation moderates American beliefs about climate change on educational attainment and self-reported understanding of the issue.…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%